TRANSFORMASI PERILAKU KONSUMTIF MAHASISWA DI PERANTAUAN (STUDI KASUS MAHASISWA EKONOMI SYARIAH UINFAS BENGKULU ) - Novranda, Fahmi; Idwal; Romi Adetio Setiawan (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
The aim of this research is to determine and explain student consumption behavior patterns, and to determine the factors that cause the transformation of student consumptive behavior in overseas sharia economics study programs at Fatmawati Sukarno State Islamic University, Bengkulu. This research uses a qualitative method with a case study approach, data collection techniques are interviews, observation and documentation. The social situation used in this research was 15 sharia economics study program students class of 2019. The data analysis technique used was the Miles and Huberman model. From the results of the research and discussion, it was found that the transformation of consumptive behavior of overseas students at Fatmawati Sukarno University, Bengkulu, sharia economics study program, among others, in terms of prioritizing consumption, they prioritize needs rather than desires, in terms of choosing goods for consumption, many of them do not pay attention to the type of goods, cleanliness. or the price, using branded goods to gain appreciation and high social status, discounting prices, bargaining, and spending free time hanging out in cafes and coffee shops. Coffee shops are just places to relax and have fun. This is what makes them trapped in consumer behavior. The aim of this research is to determine and explain student consumption behavior patterns, and to determine the factors that cause the transformation of student consumptive behavior in overseas sharia economics study programs at Fatmawati Sukarno State Islamic University, Bengkulu. This research uses a qualitative method with a case study approach, data collection techniques are interviews, observation and documentation. The social situation used in this research was 15 sharia economics study program students class of 2019. The data analysis technique used was the Miles and Huberman model. From the results of the research and discussion, it was found that the transformation of consumptive behavior of overseas students at Fatmawati Sukarno University, Bengkulu, sharia economics study program, among others, in terms of prioritizing consumption, they prioritize needs rather than desires, in terms of choosing goods for consumption, many of them do not pay attention to the type of goods, cleanliness. or the price, using branded goods to gain appreciation and high social status, discounting prices, bargaining, and spending free time hanging out in cafes and coffee shops. Coffee shops are just places to relax and have fun. This is what makes them trapped in consumer behavior.